2010
DOI: 10.1002/stco.201010029
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of stiffeners for stainless steel trapezoidal sheeting

Abstract: The calculation of the loadbearing capacity of thin‐walled structures, including trapezoidal sheeting, normally follows the procedures of EN 1993‐1‐3 and similar codes. EN 1993‐1‐4 complements this standard for thin‐walled structures made of stainless steel. Unfortunately, a buckling curve for stiffeners between the plane cross‐section parts of the flanges or the webs is lacking. A finite element analysis was performed in order to obtain a buckling curve for such stiffeners. The finite element model was calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…It is clear from the comparison of the above mentioned buckling curves, that the resulting points from the parametric study are corresponding the best to the curve proposed by Misiek et al (2010). However, there is a considerable deviation of the results for lower slendernesses of the stiffener.…”
Section: Parametric Studymentioning
confidence: 70%
See 2 more Smart Citations
“…It is clear from the comparison of the above mentioned buckling curves, that the resulting points from the parametric study are corresponding the best to the curve proposed by Misiek et al (2010). However, there is a considerable deviation of the results for lower slendernesses of the stiffener.…”
Section: Parametric Studymentioning
confidence: 70%
“…3). The comparison is done with the codified distortional buckling curves for carbon steel and for aluminium, and with the buckling curve proposed by Misiek et al (2010). There are three separate charts, each one for a different material type.…”
Section: Parametric Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that at room temperature, PIR cores had shown greater load-bearing capacity than MW cores. Stainless steel trapezoidal sheeting is used for applications with higher requirements regarding appearance or corrosion resistance, and they provide higher bending resistance than flat sheetings (Misiek et al, 2010). Vignesh Iyer et al (Iyer et al, 2018) carried out a comparative study between the three-point and four-point bending of rigid glass epoxy sandwich composites.…”
Section: Introductionmentioning
confidence: 99%